Sociological Analysis of Islamic Law on Family Resilience in Cases of Psychological Violence in the Household - Mirza Elmy Safira; Soepardi Redjo (Civiliza Publishing, 2026)
This study conducts a literature review on the sociological analysis of Islamic law concerning family resilience in cases of psychological violence in the household. Psychological violence, often normalized and invisible, systematically erodes the foundational elements of a healthy family, such as trust, security, and mutual respect. Employing a qualitative approach to library research, this study analyzes how social constructions and distorted understandings of Islamic legal texts perpetuate such violence. The findings reveal that patriarchal culture, reinforced by textual and partial interpretations of concepts like qawwamah and nusyuz, creates unequal power relations that legitimize psychological abuse. This distortion, combined with the victim's lack of awareness and societal silence, severely undermines authentic family resilience. Consequently, achieving genuine family resilience post-violence necessitates a fundamental reconstruction of the marital relationship. This reconstruction requires the perpetrator's acknowledgment of wrongdoing, comprehensive recovery for the victim, equitable role distribution, healthy communication patterns, and constructive conflict management, all grounded in a just and contextual reinterpretation of Islamic values. The study contributes an integrative framework for understanding and addressing psychological violence from a socio-legal perspective.